Freedom of expression and tolerance in a polarized society: a historical-philosophical study from the perspective of Voltaire thinking (Research, Society and Development, 2022)
The present work seeks to trace a historical-philosophical panorama of how freedom of expression and tolerance were constituted through the historical landmarks of humanity, using as a guide the ideologies of philosophers of the seventeenth and eighteenth century, with a main focus on the thoughts of the illustrious Philosopher-Enlightenment François-Marie Arouet, known by the pseudonym Voltaire. We present, initially, a conceptual approach about the process of formation of freedom of expression. Next, we discuss Voltaire's "Treaty on Tolerance" and its respective impacts on society. Finally, we discuss democracy in a polarized society, using the Federative Republic of Brazil as the center of the approach. To this end, a historical-normative analysis was constituted about freedom of expression present in Brazilian history until the advent of the federal constitution of 1988.